The determinants of unemployment: CSEE countries panel data analysis - Jurica Bosna (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
This paper deals with the analysis of the determinants of unemployment for the Central-Eastern and South-Eastern (CSEE) European countries: Poland, Czech Republic, Slovakia, Hungary, Romania, Bulgaria and Croatia. The comprehensive analysis for the observed period from 2012 to 2020 provides important insights into the homogeneity of the determinants of unemployment and the efficiency of the CSEE labour markets. A panel analysis has been conducted by OLS-PCSE method for CSEE countries and an additional analysis for two CEE and SEE subsamples. Gross fixed capital formation, interest rate and active labour market policies had a statistically significant impact on CSEE panel level, which was confirmed by the analysis conducted on subsamples. Active labour market policies expenditures had a stronger impact on reducing unemployment compared to gross fixed capital formation. Only the interest rate had a positive statistical effect on unemployment. Macroeconomic and institutional variables had almost identical effects on unemployment and their labour markets reacted very similarly. ALMP had the strongest impact on unemployment trends of the observed groups of countries. Further increased expenditures in ALPM policies and their complementary with PLMP are needed in a manner to further enhance labour market efficiency.
Keywords: E02; J01; J11; 330; Labour market; Unemployment; Panel data analysis; CSEE; CEE; SEE